2005
DOI: 10.1021/jo0507542
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2‘-C-Difluoromethylribonucleosides and Their Enzymatic Incorporation into Oligonucleotides

Abstract: [Chemical reaction: See text] Nucleosides bearing a branched ribose have significant promise as therapeutic agents and biotechnological and biochemical tools. Here we describe synthetic entry into a new subclass of these analogues, 2'-C-beta-difluoromethylribonucleosides. We constructed the glycosylating agent 4 in three steps from 1,3,5-tri-O-benzoyl-alpha-D-ribofuranose 1. The key steps included nucleophilic addition of difluoromethyl phenyl sulfone to 2-ketoribose 2 followed by mild and efficient reductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 53 publications
(102 reference statements)
0
17
1
Order By: Relevance
“…It has been shown that NH 3 can efficiently remove the benzoyl group of protected uridine when the incubation was performed at 4°C for 24–48 h [2425]; however, in our case, incubation with NH 3 at 50°C for 5 min resulted in incomplete deprotection and unidentified byproducts. We also observed that presence of SnCl 4 reduced the overall yield of the desired final product (β-anomer) than expected from the coupling step.…”
Section: Resultscontrasting
confidence: 58%
“…It has been shown that NH 3 can efficiently remove the benzoyl group of protected uridine when the incubation was performed at 4°C for 24–48 h [2425]; however, in our case, incubation with NH 3 at 50°C for 5 min resulted in incomplete deprotection and unidentified byproducts. We also observed that presence of SnCl 4 reduced the overall yield of the desired final product (β-anomer) than expected from the coupling step.…”
Section: Resultscontrasting
confidence: 58%
“…The difluoromethyl moiety has been widely used to modify physical, chemical and biological properties of organic molecules. Although, several methods for the synthesis of difluorometylated derivatives are available [7][8][9][10][11][12][13], only few protocols of FMST synthesis on a large scale have been reported to date [14][15][16]. According to the literature synthetic strategies the difluoromethyl α-substituted styrene was prepared by two-step procedure, where a key step involved a nucleophilic addition of Page 6 of 17 A c c e p t e d M a n u s c r i p t either Gringard's reagent (phenylmagnesium bromide [14]) or organolithium (methyllithium [15]) to corresponding gem-difluorinated ketones.…”
Section: *Manuscriptmentioning
confidence: 99%
“…303 Their method commenced with the construction of the glycosylating agent 792 in several steps from 1,3,5-tri-O-benzoyl-a-D-ribo-furanose 789, and the key steps included the nucleophilic addition of PhSO 2 CF 2 H to the ketone 790 followed by mild and efficient reductive desulfonation (Scheme 121). Glycosylation of the compound 792 with bis (trimethylsilyl)uracil and subsequent debenzoylation gave the difluoromethyluridine 793 (B¼U).…”
Section: Difluoromethylated or Difluoromethylenated Nucleosidesmentioning
confidence: 99%